Analisis Pendapatan Dan Nilai Tambah Produk Olahan Nanas Koperasi Produsen Miwa Pineapple Kota Prabumulih - Nadia, Nadia; Umikalsum, R.A.; Azmi, Nur (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Miwa Pineapple Producer Cooperative (Mitra Iwari) Prabumulih City was established in 2022 and is engaged in the business of producing pineapple leaf fiber and other processed pineapple products such as pickled pineapple, pineapple candy and pineapple syrup. The Miwa Pineapple Producer Cooperative was created based on the needs of its members and farmers as well as residents domiciled in Prabumulih City in order to participate in preserving and redeveloping pineapple cultivation in Prabumulih City. One of the processed products of this cooperative is various processed pineapple products, to increase added value and selling prices. This study aims to see the income and added value of processed pineapple products at the Miwa Pineapple Producer Cooperative. The method used in this study is the case study method. The analysis used in this study is income analysis and hayami value added analysis. The results of the study showed that the fixed costs per month for pickles, pineapple syrup and pineapple candy at the Miwa Pineapple Producer Cooperative were Rp34,903, Rp36,125 and Rp36,152. The variable costs per month for pickled pineapple, pineapple syrup and pineapple candy were Rp1,211,000, Rp1,300,000 and Rp1,340,000. The total costs per month for pickled pineapple, pineapple syrup and pineapple candy were Rp1,245,903, Rp1,326,125 and Rp1,413,903. The monthly income for pickled pineapple was Rp4,000,000, pineapple syrup was Rp4,000,000, and pineapple candy was Rp7,680,000. The monthly income of pickled pineapple is Rp2,754,097, pineapple syrup is Rp2,673,875, and pineapple candy is Rp6,226,375. The added value of pickled pineapple is Rp242,400, pineapple syrup is Rp248,000, and candy is 312,000. Pineapple candy produces a higher level of company profit with a profit of 96.40%, compared to pickles of 96.40% and syrup94.06 of 18%.